Pengaruh inovasi produk terhadap loyalitas pelanggan: Mediasi keputusan pembelian, moderasi usia dan konformitas sosial - Fiska Mekar Kustiani; Damelina Basauli Tambunan; Teofilus Teofilus (MBR (Management and Business Review), 2025)
This study examines the effect of product innovation on customer loyalty, focusing on purchase decision as a mediating role and age group and social conformity as moderating effects. Using a quantitative approach, this study applied regression analysis to questionnaire data, with a purchase frequency of three times in February 2025. The results show that product innovation has a positive effect on customer loyalty, product innovation has a positive effect on purchasing decisions, purchasing decisions have a positive effect on customer loyalty, purchasing decisions act as a mediating variable in the relationship between product innovation and customer loyalty, age group moderates the relationship between product innovation and customer loyalty at all ages, and social conformity strengthens the relationship between product innovation and purchasing decisions for consumers aged ≤ 34 years, while the same variable tends to weaken the relationship for consumers aged > 34 years.